Microfluidic Systems to Study Neutrophil Forward and Reverse Migration - Babatunde, Kehinde Adebayo; Ayuso, Jose M.; Kerr, Sheena C.; Huttenlocher, Anna; Beebe, David J. (Frontiers in Immunology, 2021)
During infection, neutrophils are the most abundantly recruited innate immune cells at sites of infection, playing critical roles in the elimination of local infection and healing of the injury. Neutrophils are considered to be short-lived effector cells that undergo cell death at infection sites and in damaged tissues. However, recent in vitro and in vivo evidence suggests that neutrophil behavior is more complex and that they can migrate away from the inflammatory site back into the vasculature following the resolution of inflammation. Microfluidic devices have contributed to an improved understanding of the interaction and behavior of neutrophils ex vivo in 2D and 3D microenvironments. The role of reverse migration and its contribution to the resolution of inflammation remains unclear. In this review, we will provide a summary of the current applications of microfluidic devices to investigate neutrophil behavior and interactions with other immune cells with a focus on forward and reverse migration in neutrophils.